Pemberdayaan Guru dalam Upaya Pencegahan Perilaku Perundungan (Bullying) di Sekolah Dasar - Marhadi, Hendri; Erlisnawati, Erlisnawati; Risma, Devi; Alpusari, Mahmud; Elmustian, Elmustian; Fatmawilda, Fatmawilda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This community service activity aims to (1) increase teachers' understanding of the forms of bullying in elementary schools and (2) increase teachers' ability to identify and prevent bullying behavior in elementary schools. Achieving these goals is carried out through training using lecture methods, questions and answers, demonstrations and exercises (tutorials). The activity began with a focus group discussion (FGD) activity which was attended by various parties. After the training activities, monitoring or evaluation is carried out by the activity implementation team to monitor and assist teachers in completing the task of identifying and preventing bullying in elementary schools. The results of the service show that the community service program is running well and smoothly. This program is able to provide teachers with an understanding of how to identify forms of bullying and how to take preventative action. The suggestions that can be made from the results of this community service program are that elementary school teachers are expected to have motivation and always cultivate a caring attitude towards the students' learning environment. Education practitioners are expected to always be able to assist elementary school teachers in activities related to the learning process.